LEARNING RESOURCES BY ENVIRONMENT SEBAGAI VISUALISASI MANAJEMEN SARANA PRASARANA PENDIDIKAN DI MIN JEJERAN BANTUL - Nadhiroh, Siti; Jannah, Rina Roudhotul (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2016)
This research based development and progress educational world wanted increase power creativeness and innovation from educators today. Visualize of educator’s credibility competence not only seen from the speed finish lessons. But, which the process optimize management of facilities and infrastructures, so as create learning resources by environment of school. The research is the qualitative study by taking background in MIN Jejeran Bantul Yogyakarta. The research results show that management of facilities and infrastructures includes activities of planning, pengiventarisan, the use of, maintenance, the removal of, and accountability also improve educator’s creativeness and enrich scientific who can be integrated to learning would also take morality school tuition to better understand in concrete terms and protecting the environment around.